Computational Systems Biology - McDermott, Jason; Samudrala, Ram; Bumgarner, Roger; Montgomery, Kristina; Ireton, Reneé (Methods in Molecular Biology, 2009)
XVIII, 587 p. 130 illus., 3 illus. in color.